AERODYNAMIC PERFORMANCE OF SMALL-SCALE HORIZONTAL AXIS WIND TURBINES UNDER TWO DIFFERENT EXTREME WIND CONDITIONS - ALPMAN, EMRE (YILDIZ TECHNICAL UNIV, 2015)
Aerodynamic performance of two small-scale horizontal axis wind turbines are analyzed under the extreme operating gust and extreme direction change conditions with initial wind speeds of 7, 10, 13, 15 and 20 m/s. Performance predictions are performed using computational fluid dynamics, and time variations of shaft torque and hub bending moment produced by the turbines are presented and compared with each other. Sectional flow field and sectional blade loading details along with surface skin friction line predictions are also presented in order to explain the loading behavior of the turbine blades at the mentioned extreme wind conditions. Predictions show that variations in wind speed and blade loadings are similar at low wind speeds, however, this similarity degrades as the wind speed increases. Also compared to wind speed changes, aerodynamic forces are shown to adapt more slowly to wind direction changes.
Keywords: Horizontal axis wind turbines; extreme wind conditions; computational fluid dynamics